Analisis Kekuatan Tarik Komposit Termoseting Hibrid Serat Bambu -E-Glass/ Epoxy Unidirectional 0° Vs Hibrid Serat Bambu E-Glass WR/ Epoxy dan Aplikasinya Pada Struktur Frame Quadkopter - Lies Banowati Banowati; Kresna Adhy Putra; Ruslan Abdul Ghani (Institut Teknologi Dirgantara Adisutjipto, 2022)
The uses of natural fiber in composite structures have increased recently. These fibers are considered ‘green’ and foreseen as an alternative fiber substitute in the furture. The aim of the research is to obtain the mechanical characteristics of the hybrid thermosetting composites with bamboo-E-Glass fiber reinforcements by using epoxy as matrix. The fibers were arranged to make a unidirectional 0° and bidirectional (0°/90°). Composite manufacturing method used hand lay-up and vacuum bagging. Tensile test conducted according to standard size ASTM D3039, and the results were analyzed using two parameters Weibull distribution. The results showed that the hybrid thermosetting bamboo-E-Glass composites have potentials to be made as quadcopter frame structures.